Atomic structure of grain boundaries in UO2 Bicrystals: A coupled high resolution transmission electron Microscopy/Atomistic simulation approach. (1st January 2022) - Bourasseau, Emeric; Onofri, Claire; Ksibi, Amani; Iltis, Xavière; Belin, Renaud C.; Lapertot, Gérard
Abstract: In this work, high resolution transmission electron microscopy and numerical simulation at the atomic scale were coupled, for the first time to our knowledge, to study the atomic structure of two Σ5 symmetric tilt grain boundaries in uranium dioxide (UO2 ) bicrystals. We show that whereas the Σ5 (021)/[100] is fully symmetric, with the grain boundary plane forming a mirror symmetry plane, a rigid body translation exists between the crystals in the Σ5 (031)/[100]. We particularly believe that the excellent agreement between experimentally observed and simulated structures highlights the relevance of the coupled approach. Such result emphasize that the use of CRG and Yakub empirical potentials including a Morse contribution can be relied upon to model the behavior of UO2 . Graphical abstract: Image, graphical abstract